Pharmacological properties of the repellent secretion of Zonocerus variegatus (Orthoptera: Prygomorphidae) - Idowu, A B; Idowu, O A (Revista de Biología Tropical, 1999)
The odours of the whole body and the secretion of Zonocerus variegatus were easily recognised and perceived by human volunteers. However, the secretion odour is not related to the odour of the food plant consumed by the grasshopper. The repellency of Z. variegalus becomes more pronounced in the 6th. and adult instars whose gland lumens contain an appreciable volume of secretíon. The seeretion odour is so strong that even dilulion does no! affee! its repulsiveness to humans. The secretion had pharmacological properties: it indueed contraction in rat (Rattus rattus) stomach smooth musc1e preparations and guinea pig (Cavia porcellus) ileum, and induced oedema formation in the rat hind paw. The secretion was not lethal to the animal s used in this study, effects were temporary and reeovery oecurs after a short time.